2012
DOI: 10.1111/and.12011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the seminiferous tubules in oligoasthenoteratozoospermic men associated with varicocele

Abstract: Varicocele is associated with venous reflux that may cause increased heat and interstitial pressure within the testes, with variable pathological effects on spermatogenesis. This study aimed to study the ultrastructural testicular changes in the seminiferous tubules of 20 infertile severe oligoasthenoteratozoospermia (OAT) men associated with varicocele and five patients with obstructive azoospermia without varicocele as controls. They were subjected to testicular biopsy which was evaluated by transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“… 78 Ultrastructurally, seminiferous tubules from men with varicocele demonstrate thickening of the germinal epithelium with increased apoptosis, Sertoli and germ cell cytoplasmic vacuolization, and alterations in spermatids and spermatozoa. 79 …”
Section: Testicular Effects Of Varicocelementioning
confidence: 99%
“… 78 Ultrastructurally, seminiferous tubules from men with varicocele demonstrate thickening of the germinal epithelium with increased apoptosis, Sertoli and germ cell cytoplasmic vacuolization, and alterations in spermatids and spermatozoa. 79 …”
Section: Testicular Effects Of Varicocelementioning
confidence: 99%
“…Using transferrin immunolabeling 30,70 we showed that left-sided varicocele caused a decrease in both global and VII/VIII stage-specific transferrin in rats, indicating a functional alteration in the Sertoli cell. Under normal conditions, transferrin mRNA levels vary twofold across the complete cycle, being high during the stages XII to XIV and achieving its maximum at stages VII and VIII.…”
Section: Discussionmentioning
confidence: 89%
“…Taking into account the possible occurrence of structural and metabolic alterations in Sertoli cells under abnormal conditions that involve oxidative stress, the relevant role of these cells for the establishment and regulation of spermatogenesis, and the scarce number of research works discussing the importance of Sertoli cell damage in the varicocele development, 14,30,31 we decided to study the impact of varicocele on the alteration in the function and structure of Sertoli cell and its involvement in the loss of integrity of the seminiferous epithelium. As varicocele has a higher occurrence on the left side 5,32,33 and is commonly established early in puberty, 34 but is clinically diagnosed only during sexual maturity, 35 we decided to experimentally induce the left-sided varicocele in peripubertal rats, as this model can provide a scrutiny about the impairment of Sertoli cell in adulthood and its key role in spermatogenic injury triggered from sexual immaturity.…”
Section: Introductionmentioning
confidence: 99%
“…Vacuoles in Sertoli cells are derived from smooth endoplasmic reticulum and are commonly found in human VC patients and other pathologies such as cryptorchidism and idiopathic infertility (Terquem & Dadoune, 1981). The lesions in Sertoli cells suggest the impairment of support function, and Sertoli cells are incapable to support germ cells with subsequent sloughing from the spermatogenic epithelium (El‐Kamshoushi, Zohdy, Abou Khedr, Nabhan, & Mostafa, 2013). Therefore, germ cell disorganisation and loss were seen in the lumen of testes and abnormally developmental spermatozoa such as doubled‐head and abnormal mitochondria arrangements were observed.…”
Section: Discussionmentioning
confidence: 99%